Bifunctional cysteine-engineered CAR-T cells enable thiol-mediated targeting to overcome antigen escape in B cell lymphoma - Lühle, Jost; Krost, Simon; Goerdeler, Felix; Valentí, Aina; Shanin, Elena; Seitz, Christian; Seeberger, Peter H.; Moscovitz, Oren (ACS central science, 2025)
Chimeric antigen receptor (CAR) T cell therapy has revolutionized the treatment of hematologic malignancies; however, durable remissions remain limited due to antigen-negative cancer relapse, where tumor cells downregulate or lose the targeted antigen to evade immune recognition. To address this challenge, we developed cysteine-engineered CAR (CysCAR) T cells that redirect T cells to target cancer cells based on extracellular redox imbalances and the altered thiol/disulfide ratios, a marker we identified on B cell lymphomas. Here, we show that CysCAR-T cells, engineered with different cysteine-modified antibody fragments, exhibit a potent and specific cytotoxicity in vitro across various B cell lymphoma (BCL) subtypes, even in antigen escape models. Moreover, by integrating cysteine engineering with clinically used anti-CD19 CAR-T cells, we enabled simultaneous targeting of CD19 and altered redox states on BCL, potentially reducing the risk of antigen escape. In a pilot in vivo study, these bifunctional CD19-CysCAR-T cells suppressed tumor growth and prolonged survival of BCL-bearing mice without inducing systemic toxicity. Given that aberrant exofacial redox states are a hallmark of multiple cancers, our findings suggest a promising strategy to enhance the efficacy of anti-CD19 CAR-T cell therapy, overcome antigen escape, and reduce tumor relapse in BCL, with potential applicability to other malignancies.
Gesehen am 12.12.2025